Study about mean sea level determination with altimetry satellite - Reis, Vânia Pereira (2018)
The shape attributed to the Earth, by convention, is the geoid. This is considered as the equipotential surface which coincides with the undisturbed Mean Level of the Seas (MSL). It is of fundamental importance to geodesists determining the MSL (altimetric Data), since this play an important role in the realization of global reference systems and enable the integration of data referred to classic vertical networks, where each datum is defined by the MSL. Currently altimetry satellite (ALTSAT) is an effective technique for monitoring the MSL, as it provides a methodical and continuous data collection and that in turn allows the global observation of the sea level (SL). Resulting in a data structure with several oceanographic parameters and time series of consistent data for long periods. This greatly facilitates the use of these data for studies of NMM and, hence, the determining of the Mean Dynamic Topography (MDT) and geoid itself. This paper focuses on the study of obtaining MSL obtained by altimetry missions, focusing on TOPEX/Poseidon, Jason-1, Jason-2 and Jason-3 satellites aiming the importance of MSL for MDT determination.